Pengaruh dan Pertimbangan Faktor Lingkungan untuk Peningkatan Kualitas pada Lini Produksi - H Harisupriyanto (Department of Mechanical Engineering, University of Udayana, 2014)
Pemborosan (waste) yang berasal dari proses produksi muncul sebagai indikasi adanya problem dandampak terhadap lingkungan, kesehatan dan keselamatan kerja.Indikasi wastetersebutadalahakibatdaridefect waste di mesin finishing dan waiting waste di mesin mounting. Defect waste yang tinggimengakibatkan Environment, Health and Safety (EHS) waste yang tinggi pula. Untuk itu perusahaanharus melakukancontinous process improvement yang terus menerus.Tujuan yang ingin dicapaiadalah identifikasi waste di proses produksi, mencari akar penyebab permasalahan dan memberikanalternatif solusi yang dapat dilakukan perusahaan untuk mengurangi dampak timbulnyawasteIdentifikasi waste dilakukan berdasarkan pada, E-DOWNTIME yakni sembilan jenis waste.Jenis waste ini meliputi Environmental, Safety, and Health (EHS), Defect, OverProduction, Waiting,Not utilizing employee, Transportation, Inventory, Motion, dan Excessive processing waste. Untukmemetakan proses yang mengindikasikan adanya waste (pemborosan), diperlukan value streammapping.Pemetaan tersebut bertujuan untuk mencari critical waste.Berdasarkan pada critical wastemaka dicari akar permasalahan yang dapat dirunut dengan penggunaan RCA (root cause analisys).Untuk mencari prioritas resiko yang paling tinggi terhadap wastediperlukan FMEA (failure mode andeffect analisys). Dengan adanya prioritas tersebut maka alternatif solusi dapat dihasilkan.Alternatifperbaikan yang diusulkan adalah pembentukan timTotal Productive Maintenance, perbaikan kualitasproduk, serta eksperimen terhadap pengurangan pemakaian komponen. Dengan pendekatan valuemanagementmakapembentukan dan pelatihan untuk timTotal Productive Maintenance adalahalternatif terbaiknya. Hasil akhir dari alternatif ini adalah meningkatnya nilai sigmaproduk dari 2,91menjadi 3,08 Kenaikan sigmatersebut memberikan indikator perbaikan pada lini produksi dandampak lingkungan.Kata Kunci: EHS, waste, RCA, FMEA, sigma.Waste that comes from the process of production appears as an indication of the problem and theimpact on the environment, health and safety. The waste is the result of a defect in the finishingmachine and waste waiting in the engine mounting. Defect high waste resulting Environment, Healthand Safety (EHS) waste is also high. Therefore, the company must conduct a continuous process ofcontinuous improvement. The goal is to identify waste in the production process, find the root causeof the problem and provide alternative solutions that can be done by the company to mitigate theimpact of the emergence of waste. Waste identification is done based on the E-DOWNTIME whichconsists of nine types of waste. This type of waste includes Environmental, Safety, and Health (EHS),Defect, Over Production, Waiting, Not utilizing employee, Transportation, Inventory, Motion, andExcessive waste processing. To map the process that indicates a required waste value streammapping. The mapping aims to find critical waste. Base on critical waste then look for the root causescan be traced to the use of RCA (root cause analysis). To search for the most high-risk priority towaste FMEA (failure mode and effect analysis) is needed. With the priority is the alternative solutioncan be generated. Alternatives proposed improvement is the formation of a team of Total ProductiveMaintenance, improvement of product quality, as well as experiments on reducing the use ofcomponents. With the value management approach, the establishment and training of a team of TotalProductive Maintenance is the best alternative. The final result is the increasing alternative sigmavalue of the product becomes 3.08 2.91. The increase in the sigma provides an indicator ofimprovements on production lines and environmental impact.Kata Kunci: EHS, waste, RCA, FMEA, sigma